2023
DOI: 10.1007/s13202-022-01601-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polypropylene fiber on the curing time of class G oil well cement and its mechanical, petrophysical, and elastic properties

Abstract: The cement paste is subjected to various loads throughout a well’s life, which may compromise some of its essential characteristics and impair its performance. When the cement paste is first being formed and the cement’s characteristics have not yet fully matured, these loadings take on greater importance. In this study, the early properties of cement used in oil wells that contains polypropylene fiber are assessed. Five different curing times were used to prepare ten cement samples (6, 12, 24, 48, and 72 h). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There are other studies stating that there is a decrease in the pore structure with the use of PP fiber. For example, Ahmed et al [31] reported in his study that the porosity of the sample produced only with cement was 21.2% after 48 h of hydration, while the porosity of the sample containing PP fiber was 19.2% after the same period. It is thought that this is because PP fibers have a high specific surface and thus accelerate the hydration kinetics.…”
Section: Resultsmentioning
confidence: 98%
“…There are other studies stating that there is a decrease in the pore structure with the use of PP fiber. For example, Ahmed et al [31] reported in his study that the porosity of the sample produced only with cement was 21.2% after 48 h of hydration, while the porosity of the sample containing PP fiber was 19.2% after the same period. It is thought that this is because PP fibers have a high specific surface and thus accelerate the hydration kinetics.…”
Section: Resultsmentioning
confidence: 98%
“…Some of these techniques analyze the cement's reaction rate, while others analyze the cement's chemical or physical properties at various times [42,43]. For example, Ahmed et al [44] investigated the impact of adding polypropylene fiber to class G oil well cement on its curing time and various properties. The study found that the addition of polypropylene fiber enhanced the cement's strength, reduced porosity and permeability, and increased elasticity.…”
Section: Introductionmentioning
confidence: 99%